2021
DOI: 10.1148/radiol.2021204141
|View full text |Cite
|
Sign up to set email alerts
|

CT-derived Chest Muscle Metrics for Outcome Prediction in Patients with COVID-19

Abstract: Background Lower muscle mass is a known predictor of unfavorable outcome, but its prognostic impact on COVID-19 patients is unknown. Purpose To investigate the contribution of CT-derived muscle status in predicting clinical outcomes in COVID-19 patients. Materials and Methods Clinical/laboratory data and outcomes (intensive care unit [ICU] admission and death) were retrospectively retrieved for patients with reverse transcriptase polymerase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 34 publications
2
73
3
Order By: Relevance
“…Nowadays, the assessment of body composition represents a cornerstone in nutritional science, due to its prognostic value in different clinical conditions [33]. Schiaffino et al observed that low muscle mass detected by CT scans was independently associated with in-hospital mortality and ICU admission among COVID-19 patients [34]. On the contrary, a retrospective study observed that bioimpedance analysis does not appear to bring further predictive value than nutritional risk screening alone [35].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the assessment of body composition represents a cornerstone in nutritional science, due to its prognostic value in different clinical conditions [33]. Schiaffino et al observed that low muscle mass detected by CT scans was independently associated with in-hospital mortality and ICU admission among COVID-19 patients [34]. On the contrary, a retrospective study observed that bioimpedance analysis does not appear to bring further predictive value than nutritional risk screening alone [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sarcopenia has been also reported as an independent factor associated with intensive care unit admission and mortality in patients hospitalized for COVID-19 pneumonia (Fig. 1 ) [ 24 ]. In inflammatory bowel disease, sarcopenia has a prevalence ranging from 27 to 61% [ 25 ], and is proven to be a negative prognostic factor for intestinal resection, especially in patients with Crohn’s disease [ 26 ].…”
Section: Clinical Impact Of Sarcopeniamentioning
confidence: 99%
“…It is frequently possible to conduct a CT-based estimation of muscle mass since patients who are hospitalized are often imaged as a part of their diagnostic work-up. An observational study found that a decreased paraspinal muscle area at the level of the 5 th thoracic vertebra correlated with an increased risk of ICU admission and death in hospitalized adults and elderly patients (median age 65 years) with a COVID-19 infection who were scanned as a part of their routine care [123]. Another cohort study with patients whose median age was 62 years showed that those patients defined as sarcopenic on the basis of their skeletal muscle index (cross-sectional muscle area measured at the level of the 12 th thoracic vertebra) experienced a longer duration of hospital stay and were more likely to die from the infection [124].…”
Section: The Ct-determined Loss Of Skeletal Muscle Mass In Clinical Contextmentioning
confidence: 99%